Ensino de gramática em aulas de inglês língua estrangeira: relações entre cognição relatada, prática pedagógica e contexto - Furlan, Cláudia Jotto Kawachi (Universidade Federal de São Carlos, 2014)
The aim of this work is to analyze participants reported cognition, their practice and the teaching context influence in regard to English as a Foreign Language (EFL) grammar teaching. According to Borg (2006), language teaching can be seen as a process that is defined by dynamic interactions among cognition, context and experience. The interest in investigating the cognition of novice teachers in relation to grammar teaching was based on the fact that the participants were educated on the studies of Batstone (1994) and Larsen- Freeman (2003). Both authors defend the view of grammar centered in the possibility of developing it as a skill (grammar as a skill / grammaring). Aiming at presenting and discussing possible connections among theoretical education, reported cognition, pedagogical practice and teaching context influences, we adopted the following data collection instruments and procedures: semi structured interviews, questionnaire, class observation, class recordings and stimulated recall interviews. The participants of this study are EFL teachers who had recently graduated from the same institution and taught, when data were collected, in two different teaching contexts. Based on the data analysis, it was possible to classify participants into three groups, which show different results in regard to grammar teaching. These findings show teaching contexts have influenced teachers practice, mainly regarding the possibility of integrating form and communication, considering the development of grammar as skill. In addition, it was possible to provide some insight into the area of teacher education reflecting about the relationship between theory and practice, aiming at developing efficient and meaningful EFL teaching in different educational contexts.
Keywords: Língua inglesa - ensino e aprendizagem; Língua inglesa - gramática - estudo e ensino; Cognição de professores; Contextos educacionais; Teoria e prática; Teaching grammar; Teachers cognition; Educational contexts; Relationships between theory and practice; LINGUISTICA, LETRAS E ARTES::LINGUISTICA